KONSEP HALAL LIFESTYLE MENURUT AL-GHAZALI DAN IBN KHALDUN: STUDI KOMPARATIF DALAM PERSPEKTIF EKONOMI ISLAM - Faza Nazlatuz Zahira; Muhammad Yazid; Abdur Rohman Rohman (Universitas Al-Amien Prenduan, 2026)
The development of halal lifestyle in recent years shows the expansion of the meaning of religious practices into part of the global halal lifestyle and industry. On the other hand, various studies show that Muslim consumption practices are still influenced by consumptive behavior and symbolic orientation towards halal products, so that a conceptual study of halal lifestyle is needed from an Islamic economic perspective. This study aims to comparatively analyze the concept of halal lifestyle according to Al-Ghazali and Ibn Khaldun and to compile a conceptual synthesis relevant to the development of halal lifestyle from an Islamic economic perspective. This study uses a qualitative approach with library research. The unit of analysis is the concepts of halal lifestyle in the books Ihya' Ulum al-Din by Al-Ghazali and Muqaddimah by Ibn Khaldun. Data were analyzed using qualitative content analysis through a descriptive-comparative approach with textual hermeneutic interpretation. The results show that Al-Ghazali emphasizes qana'ah and zuhud as internal control mechanisms for consumption behavior, while Ibn Khaldun emphasizes external control through the rejection of tarafu' to maintain the sustainability of 'umran. The synthesis of these two perspectives produces a Value-Based Halal Lifestyle Model that integrates individual ethical dimensions and socio-civilizational dimensions as a conceptual framework in developing halal lifestyle studies from an Islamic economic perspective